Reproducibility in echocardiographic two- and three-dimensional mitral valve assessment - Hien, Maximilian; Großgasteiger, Manuel; Weymann, Alexander; Rauch, Helmut; Rosendal, Christian (Echocardiography, 2014)
Background Three-dimensional transesophageal echocardiography (3DTEE) has been demonstrated to provide more accurate information than two-dimensional transesophageal echocardiography (2DTEE) in the localization of mitral valve prolapse (MVP). However, most studies have been single-rater studies. Few results were tested for inter-observer variability with a single second rater. This multicenter study aimed to determine reliability of 2D and 3DTEE mitral valve evaluations by calculating inter-observer agreement between various echocardiographers. Methods Fifteen observers from 4 institutions in Germany and Switzerland interpreted 2D and 3DTEE images from 6 patients selected to represent a large spectrum of MVP diversity. Surgical findings served as reference. Individual assessments of MVP and ruptured chordae tendineae (ChR) pathology were compared by calculating Randolph's free-marginal multirater kappa coefficient. Results Accuracy of MVP evaluation with 3DTEE was 83.9%, CI [81.0%; 86.8%] and 78.7% CI [76.6% 80.8%] with 2DTEE. Flail leaflets with chordal ruptures were described correctly in 91.1%, CI [85.8, 96.4] with 3D compared to 71.1%, CI [65.0, 77.2] with 2DTEE. The multirater kappa coefficient of inter-observer agreement among all 15 observers was κ = 0.65/0.58 for 3D/2D evaluation of MVP and κ = 0.70/0.54 for detection of ChR. Conclusion Three-dimensional assessment of MVP was superior to 2DTEE, although the accuracy of both 3DTEE and 2DTEE was found to be lower than previously published. 3D MVP assessment is less operator dependent than 2DTEE evaluation. Although validity has been demonstrated before, we provide evidence that 3DTEE is reproducible among 15 observers and is a reliable method for MVP evaluation.